The Effect of Collaborative Strategic Reading Toward Students Reading Skill - Anwar, Ahmad Khoirul (Anglophile Journal, 2020)
This article aimed to improve student’s skill in reading an English text. It is used Collaborative Strategic Reading (CSR). This method consist of 4 steps those are : Preview, Click and Clunk, Get the Gist and Wrap Up with the purpose is improving students reading comprehension by working in the group. The research subject was 8 grade of SMP 1 Jogoroto. There were 18 males and 14 females in the sample of research. There were two cycle pretest and posttest, the pretest was done before the implementation of Collaborative strategic reading in the class and the posttest was done after the implementation of CSR technique in the class. The students reading skill before the teacher aplly the Collaborative strategic raeding was only 50% it because of the students not really know the pronounciation well but after the implementation of CSR technique in the class and the teacher aplly the steps in CSR technique well(preview, Click and clunk, get the gist and wrap up) the students reading skill was 100%. In term the student’s participation, the students actively answer the question from the exercise by working in a group and pay attention to the teachers’ explanation(feedback). Keywords: Collaborative Strategic Reading, Reading Comprehension, Reading Skill